QUALITY OF LIFE OF ELDERLY PEOPLE AS A SOCIAL PROBEM - Zhytynska, Maria O. (Educological discourse, 2015)
The article is devoted to the problem of the quality of life of older people. The article analyzes the main approaches to the definition of "quality of life" is the definition of "quality of life of elderly people" and defined its objective and subjective indicators.